PERSONAL TOUGHNESS AS RELEVANCE CHARACTER IN DISRUPTION ERA - Benawa, Arcadius (International Journal of Advanced Science and Technology, 2020)
This paper aims to point out the urgency of the personal toughness in disruption era, which encounters considerable challenges. With the phenomenological method and literature study, the study would lead to the purpose of this paper and show that personal toughness, which indicates with the spirit of striving for the excellence, perseverance, integrity, respect, innovative, and team-work is very urgent in disruption era. The result showed that people must build SPIRIT Characters in disruption era to adapt to the environment and the survival in the disruption era. The research concludes that the only person who has personal toughness can survive in disruption era. The implication of the study emphasizes that whoever wants to survive in the disruption era must build own toughness like striving for excellence, perseverance, integrity, respect, innovative, and team-work eventually.